Family and School Cooperation as Exemplified by Schools in Lublin During the Period of the Second Polish Republic - Okrasa, Marzena (Uniwersytet Wrocławski, 2013)
The changes that schools experienced after regaining independence generated the need to seek new ways of working with parents. It was stressed that the work should be collective, be of social character, and recruit whole groups of people related to the organizational network. Stimulating a stable cooperation of students’ parents with the school gave rise to the creation of permanent parental organizations, such as parents’ circles, class or school patronages, and the groups of parents and parents’ circles.
Keywords: parenting circles; parental organizations; class patronages; school; family